Rancang Bangun Sistem Informasi Pengorderan Air Minum RO dengan Metode Waterfall Integrasi UML di PT Gajah Tunggal Tbk - Yulianti, Henny (Jurnal Informatika Universitas Pamulang, 2021)
The increasingly high level of competition in the tire industry encourages companies to manage their human resources well. Human resources are the company's main asset which is an important element in achieving company goals and maintaining company sustainability. Every employee is an important factor that drives a high-performing compan, therefore the company strives to provide facilities for all its employees. The facilities provided by PT. Gajah Tunggal Tbk is healthy drinking water for all its employees. The problem is the process of ordering healthy drinking water is still manual, each division goes to the RO section to order drinking water and reports often do not match the needs in the field. This makes the division lose a lot of time and effort. Because of this, with the development of information technology, the solution is to build a web-based RO drinking water ordering application system. The website design method uses the Waterfall method which is integrated with the UML software development method. With Black box testing, it is proven that the design of this RO drinking water ordering application can help the activities of employees in the company in meeting the needs of drinking water and accurate reports so that it becomes effective and efficient. in the working time of employees and this can improve the performance of employees of PT. Gajah Tunggal Tbk